Deep-time climate legacies affect origination rates of marine genera - Mathes, Gregor; Kießling, Wolfgang; Steinbauer, Manuel J. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Biodiversity dynamics are shaped by a complex interplay between current conditions and historic legacy. The interaction of short- and long-term climate change may mask the true relationship of evolutionary responses to climate change if not specifically accounted for. These paleoclimate interactions have been demonstrated for extinction risk and biodiversity change, but their importance for origination dynamics remains untested. Here, we show that origination probability in marine fossil genera is strongly affected by paleoclimate interactions. Overall, origination probability increases by 27.8% [95% CI (27.4%, 28.3%)] when a short-term cooling adds to a long-term cooling trend. This large effect is consistent through time and all studied groups. The mechanisms of the detected effect might be manifold but are likely connected to increased allopatric speciation with eustatic sea level drop caused by sustained global cooling. We tested this potential mechanism through which paleoclimate interactions can act on origination rates by additionally examining a proxy for habitat fragmentation. This proxy, continental fragmentation, has a similar effect on origination rates as paleoclimate interactions, supporting the importance of allopatric speciation through habitat fragmentation in the deep-time fossil record. The identified complex nature of paleoclimate interactions might explain contradictory conclusions on the relationship between temperature and origination in the previous literature. Our results highlight the need to account for complex interactions in evolutionary studies both between and among biotic and abiotic factors.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Climate change; Evolution; Fossil record; Macroevolution; Paleoclimate

Eco-Evolutionary Dynamics of Plant–Soil Feedbacks Explain the Spread Potential of a Plant Invader Under Climate Warming and Biocontrol Herbivory - Sun, Yan; Silvestro, Daniele; Mathes, Gregor; van der Heijden, Marcel G.A.; Müller-Schärer, Heinz (Global Change Biology, 2025)
Plant–soil feedbacks (PSFs) can contribute to the success of invasive plants. Despite strong evidence that plant genetic traits influence soil microbial communities and vice versa, empirical evidence exploring these feedbacks over evolutionary timescales, especially under climate change, remains limited. We conducted a 5-year field study of the annual invasive plant, Ambrosia artemisiifolia L., to examine how selection under climate warming and biocontrol insect herbivory shapes plant population genetics, soil properties, and microbial communities. After four generations under warming and herbivory, we collected seeds of the F4 plant populations together with their conditioned soil for a common garden PSF experiment to explore how resulting PSFs patterns are influencing the performance and spread potential of Ambrosia under changing environmental conditions. This is especially relevant because our recent predictions point to a northward spread of Ambrosia in Europe and Asia under climate change, outpacing the spread of its insect biocontrol agent. We discovered that warming and herbivory significantly but differentially altered plant genetic composition and its soil microbial communities, with less pronounced effects on soil physicochemical properties. Our results indicate that both herbivory and warming generated negative PSFs. These negative PSFs favored plant growth of the seeds from the persistent soil seed bank growing in the conditioned soil under insect herbivory, and by this maintaining the Ambrosia population genetic diversity. They also enhanced the spread potential of warming-selected plant offspring, especially from warmer (southern) to colder (northern) climates. This can be explained by the observed decrease in soil pathogens occurrence under insect herbivory and by the especially strong genetic changes in plant populations under climate warming. Our findings provide insights into how climate warming and biocontrol management affect eco-evolutionary interactions between invasive plant populations and their soil environments, which are critical for predicting invasion dynamics in the context of global change.
CRIS-Team Scopus Importer:2025-03-28
Keywords: Ambrosia artemisiifolia; biological control; biological invasions; causal models; climate warming; eco-evolutionary plant–soil feedback; experimental evolution; Ophraella communa

Extinction risk controlled by interaction of long-term and short-term climate change - Mathes, Gregor; van Dijk, Jeroen; Kießling, Wolfgang; Steinbauer, Manuel J. (Nature Ecology & Evolution, 2021)
Assessing extinction risk from climate drivers is a major goal of conservation science. Few studies, however, include a long-term perspective of climate change. Without explicit integration, such long-term temperature trends and their interactions with short-term climate change may be so dominant that they blur or even reverse the apparent direct relationship between climate change and extinction. Here we evaluate how observed genus-level extinctions of arthropods, bivalves, cnidarians, echinoderms, foraminifera, gastropods, mammals and reptiles in the geological past can be predicted from the interaction of long-term temperature trends with short-term climate change. We compare synergistic palaeoclimate interaction (a short-term change on top of a long-term trend in the same direction) to antagonistic palaeoclimate interaction such as long-term cooling followed by short-term warming. Synergistic palaeoclimate interaction increases extinction risk by up to 40%. The memory of palaeoclimate interaction including the climate history experienced by ancestral lineages can be up to 60 Myr long. The effect size of palaeoclimate interaction is similar to other key factors such as geographic range, abundance or clade membership. Insights arising from this previously unknown driver of extinction risk might attenuate recent predictions of climate-change-induced biodiversity loss.
CRIS-Team WoS Importer:2021-02-12

Marine species and assemblage change foreshadowed by their thermal bias over Early Jurassic warming - Reddin, Carl J.; Landwehrs, Jan P.; Mathes, Gregor; Ullmann, Clemens V.; Feulner, Georg; Aberhan, Martin (Nature Communications, 2025)
A mismatch of species’ thermal preferences to their environment may indicate how they will respond to future climate change. Averaging this mismatch across species may forewarn that some assemblages will undergo greater reorganization, extirpation, and possibly extinction, than others. Here, we examine how regional warming determines species occupancy and assemblage composition of marine bivalves, brachiopods, and gastropods over one-million-year time steps during the Early Jurassic. Thermal bias, the difference between modelled regional temperatures and species’ long-term thermal optima, predicts a gradient of species occupancy response to warming. Species that become extirpated or extinct tend to have cooler temperature preferences than immigrating species, while regionally persisting species fell midway. Larger regional changes in summer seawater temperatures (up to +10 °C) strengthen the relationship between species thermal bias and the response gradient, which is also stronger for brachiopods than for bivalves, while the relationship collapses during severe seawater deoxygenation. At +3 °C regional seawater warming, around 5 % of pre-existing benthic species in a regional assemblage are extirpated, and immigrating species comprise around one-fourth of the new assemblage. Our results validate thermal bias as an indicator of immigration, persistence, extirpation, and extinction of marine benthic species and assemblages under modern-like magnitudes of climate change.
CRIS-Team Scopus Importer:2025-02-28